DEVELOPMENT OF LEARNING DEVICES BASED ON PROBLEM BASED LEARNING MODELS ON THE MATERIAL OF SOCIAL ARITHMETIC TO FACILITATE MATHEMATICS COMMUNICATION SKILL FOR CLASS VII SMP/MTs STUDENTS - Novalina Okta Dwi Putri; Sakur (Prodi. Pendidikan Matematika, FKIP, Universitas Riau, 2022)
This research is motivated by teachers who still have difficulty designing learning tools based on the 2013 curriculum. This study aims to produce mathematical learning tools based on a problem-based learning model to facilitate students' valid and practical mathematical communication skills. Learning tools are developed in the form of a syllabus, lesson plan (RPP), and student worksheets (LAS). The development model used is the 4-D model, in which stages are defined, designed, developed, and disseminate. The test subjects in this study were 6 class VII students. The test instrument used was a validity instrument in the form of a validation sheet to assess the appropriateness of the learning device and a practicality instrument in the form of a student response questionnaire to assess the practicality of using LAS. Based on the validation data analysis results, it is concluded that this mathematics learning tool is very valid, with the average rating for the syllabus being 3,84, for RPP is 3,76, and for LAS being 3,72. Based on the practicality data analysis results, the student response questionnaire showed a very practical category with an average assessment of 3,61.